2013
DOI: 10.1371/journal.pone.0056872
|View full text |Cite
|
Sign up to set email alerts
|

Reading “Sun” and Looking Up: The Influence of Language on Saccadic Eye Movements in the Vertical Dimension

Abstract: Traditionally, language processing has been attributed to a separate system in the brain, which supposedly works in an abstract propositional manner. However, there is increasing evidence suggesting that language processing is strongly interrelated with sensorimotor processing. Evidence for such an interrelation is typically drawn from interactions between language and perception or action. In the current study, the effect of words that refer to entities in the world with a typical location (e.g., sun, worm) o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
60
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(66 citation statements)
references
References 45 publications
5
60
1
Order By: Relevance
“…For example, smoke can be smelled from a distance but cumin cannot, yet they are both from the olfactory category. It is therefore likely that mental simulation of distance for perceptual modality is a less robust relationship than, for example, simulation of spatial height based on real-world location (e.g., Dudschig, Souman, Lachmair, de la Vega, & Kaup, 2013;Estes, Verges, & Barsalou, 2008).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, smoke can be smelled from a distance but cumin cannot, yet they are both from the olfactory category. It is therefore likely that mental simulation of distance for perceptual modality is a less robust relationship than, for example, simulation of spatial height based on real-world location (e.g., Dudschig, Souman, Lachmair, de la Vega, & Kaup, 2013;Estes, Verges, & Barsalou, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…We simulate such spatial locations based on our real-world experiences with objects. There are a number of experiments providing evidence for the perceptual simulation of spatial features (e.g., Dudschig, Souman, Lachmair, de la Vega, & Kaup, 2013;Estes, Verges, & Barsalou, 2008). Estes et al (2008) demonstrated simulation of height using a target detection task.…”
Section: Word Meaning Perceptual Simulation and Spacementioning
confidence: 99%
“…Of these, 364 were collated from items used in previous studies (Ansorge, et al, 2013;Chasteen, et al, 2010;Dudschig, et al, 2013;Estes, et al, 2008;Goodhew, McGaw, & Kidd, 2014;Gozli, Chasteen, & Pratt, 2013;Gozli, Chow, et al, 2013;Meier & Robinson, 2004;Setic & Domijan, 2007), and were items classified as having associations with up, down, or no clear vertical spatial association (neutral). A further 134 items were included that we developed and selected as likely to have associations with up, down, or no clear vertical spatial associations.…”
Section: Item Selectionmentioning
confidence: 99%
“…A growing body of studies documents the entwined relationship between concepts and space, in particular, how activating word meaning can systematically shift visual attention in space (e.g., Ansorge, Khalid, & Konig, 2013;Chasteen, Burdzy, & Pratt, 2010;Dudschig, De la Vega, & Kaup, 2015;Dudschig, Souman, Lachmair, de la Vega, & Kaup, 2013;Estes, Verges, & Barsalou, 2008;Fischer, Castel, Dodd, & Pratt, 2003;Gozli, Chow, Chasteen, & Pratt, 2013;Louwerse & Jeuniaux, 2010;Meier & Robinson, 2004;Santiago, Lupianez, Perez, & Funes, 2007;Setic & Domijan, 2007;Weger & Pratt, 2008;Zwaan & Yaxley, 2003). For example, after reading a word associated with up (such as Bsun^or Bjoy^), participants are faster to respond to subsequent visual targets above the center of the screen and slower to respond to targets below the center, whereas the reverse is true after reading a word associated with down (such as Bbasement^or Bbleak^).…”
mentioning
confidence: 99%
See 1 more Smart Citation